Garsorasib, a KRAS G12C inhibitor, with or without cetuximab, an EGFR antibody, in colorectal cancer cohorts of a phase II trial in advanced solid tumors with KRAS G12C mutation - Dan-Yun Ruan; Hao-Xiang Wu; Ye Xu; Pamela N. Munster; Yanhong Deng; Gary Richardson; Dong Yan; Myung-Ah Lee; Keun-Wook Lee; Hongming Pan; Steven Hager; Xingya Li; et al. (Signal Transduction and Targeted Therapy)
Abstract Mutations in the KRAS gene have long been implicated in the pathogenesis of colorectal cancer (CRC). KRAS G12C inhibitors overcome the “undruggable” challenge, enabling precision therapy. Garsorasib (D-1553), a highly potent and selective KRAS G12C inhibitor, has demonstrated promising anti-tumor activity and favorable safety profile in early clinical trials. We conducted an open-label, nonrandomized phase II trial (ClinicalTrials.gov, NCT04585035) to assess the safety and efficacy of garsorasib with or without cetuximab in KRAS G12C-mutated CRC. In the monotherapy cohort (n = 26), objective response rate (ORR) was 19.2% (95% CI, 6.6–39.4), disease control rate (DCR) was 92.3% (95% CI, 74.9–99.1), median progression-free survival (PFS) was 5.5 months (95% CI, 2.9–11.6) and median overall survival (OS) was 13.1 months (95% CI, 9.5-NE). In the combination cohort (n = 42), ORR was 45.2% (95% CI, 29.8–61.3), DCR was 92.9% (95% CI, 80.5–98.5), median PFS was 7.5 months (95% CI, 5.5–8.1), and median OS was not reached. Grade ≥3 treatment-related adverse events occurred in 5 (19.2%) and 6 (14.3%) patients in monotherapy and combination cohort, respectively. Garsorasib with or without cetuximab showed a promising efficacy and manageable safety profiles in heavily pretreated patients with KRAS G12C-mutated CRC, providing a potential new treatment approach for such population.